Evaluating Kahoot-Based Assessment in Arabic Language Final Exam at Madrasah Aliyah - Yulyana Dewi Nabilah; M. Abdul Hamid; Nur Hasan (Nurul Jadid University, 2026)
The use of digital tools such as Kahoot! in Arabic language examinations opens up new opportunities to improve assessment efficiency, increase student participation, and align assessment practices with contemporary educational demands. This study examines the validity, reliability, and implementation of a Kahoot-based assessment in the Arabic final exam at Madrasah Aliyah Bilingual Batu. The aim is to evaluate the quality of the test items and understand how students respond to the use of Kahoot in a formal exam setting. Using a descriptive quantitative method, the study analyzed item validity, reliability, and student perceptions through expert review, statistical tests, and a questionnaire. The findings show that the exam instrument achieved very high validity (94%) and strong reliability (α = 0.834). The student perception questionnaire also showed high validity (91%) and good internal consistency (α = 0.845). Students reported feeling more motivated, less anxious, and more comfortable during the test when using Kahoot, suggesting that digital game-based assessments can make Arabic exams more engaging and less stressful. However, several challenges were found, including unstable internet connections and limited time for answering questions. It indicates that Kahoot need more careful calibration of time limits, infrastructural readiness, and other supplementary assessment to achieve a balanced evaluation tools. Overall, the study shows that Kahoot has strong potential to help schools adopt digital assessment.